2015
DOI: 10.1007/s10494-015-9603-7
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of Flow Past Tandem Cylinders in a Channel

Abstract: The paper presents Large Eddy Simulation (LES) of flow around two circular cylinders in tandem placed in an open channel. This and the closely related situation of tandem cylinders in a passage are rich of complex flow phenomena and of considerable practical and fundamental interest. The configuration was set up to correspond closely to an experiment (Ataie-Ashtiani and Aslani-Kordkandi Flow Turbul. Combust. 90(3), 471-490 (2013)) with detailed velocity measurements. The ratio of the distance between the cylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…utilized the LES to analyze and describe complex 3 D flow around two circular cylinders in tandem placed in an open channel. 10 Weinmann, Sandberg and Doolan investigated the performance of a novel hybrid RANS/LES methodology for accurate flow and noise predictions of the NASA’s tandem cylinder experiment. 11 Numerical investigations using Scale Adaptive Simulation (SAS) turbulence model were carried out to study the flow around a circular cylinder near to a plane boundary by Grioni, Elaskar and Mirasso.…”
Section: Introductionmentioning
confidence: 99%
“…utilized the LES to analyze and describe complex 3 D flow around two circular cylinders in tandem placed in an open channel. 10 Weinmann, Sandberg and Doolan investigated the performance of a novel hybrid RANS/LES methodology for accurate flow and noise predictions of the NASA’s tandem cylinder experiment. 11 Numerical investigations using Scale Adaptive Simulation (SAS) turbulence model were carried out to study the flow around a circular cylinder near to a plane boundary by Grioni, Elaskar and Mirasso.…”
Section: Introductionmentioning
confidence: 99%
“…Qadi et al [7] presented three-dimensional large-eddy simulation (LES) of flow around two circular cylinders in tandem placed in an open channel. The three-dimensional flow characteristics were investigated with the help of the results obtained from LES.…”
Section: Introductionmentioning
confidence: 99%
“…The studies also revealed the effect of the vortical flow induced by the front cylinder on the development of vortices at the rear cylinder. Numerical simulations have also been conducted (Jester and Kallinderis, 2003;Meneghini et al, 2001;Vakil and Green, 2013;Mittal et al, 1997;AlQadi et al, 2015;Luc et al, 2016) to explore the effect of the Reynolds number and the distance between cylinders on the flow around the cylinders and the drag acting on them.…”
Section: Introductionmentioning
confidence: 99%